Assessing optimal use of the standard dose adjuvanted trivalent seasonal influenza vaccine in the elderly. Issue 15 (3rd April 2019) - Thorrington, Dominic; van Leeuwen, Edwin; Ramsay, Mary; Pebody, Richard; Baguelin, Marc
Abstract: Background: Despite a long-standing vaccination programme, seasonal influenza remains a major public health problem in England, in particular for the elderly where a significant disease burden remains despite vaccine coverage approaching the WHO target of 75%. The recently licensed adjuvanted trivalent vaccines (TIV-ADJ) have been shown to offer greater protection for the elderly compared to the standard-dose non-adjuvanted trivalent vaccines (TIV), particularly for those individuals 75 years old and above for whom the TIV has limited effectiveness. We assessed the cost-effectiveness of the TIV-ADJ for use in the elderly. Methods: We used a dynamic SEIR-type transmission model coupled with an economic evaluation framework, estimating the reduction in GP consultations, hospitalisations and influenza-attributable mortality. We assessed the optimal use of the TIV-ADJ by estimating the cost-effectiveness of programmes that used this vaccine in the 65+ and 75+ age groups. Findings: The use of TIV-ADJ is highly cost-effective for both target age cohorts with incremental cost-effectiveness ratios well below the £20, 000 per quality-adjusted life year (QALY) with over 90% probability that the vaccine is cost-effective at a cost-effectiveness threshold of £30, 000 per QALY. Interpretation: The increased protection provided across all three influenza vaccine sub-types makes TIV-ADJ a more attractive option than TIV from the perspective of the healthcare provider, driven by the increased efficacy against A(H3N2). When deciding on the optimal use of the newly available vaccine it is important to consider the fact that TIV has very limited effectiveness for the 75+ age group, who would therefore get the greatest benefit from a more effective vaccine. Funding: I-MOVE+ project (Integrated Monitoring of Vaccines in Europe) through the European Union's Horizon 2020 research and innovation programme under grant agreement #634446 and the National Institute for Health Research Health Protection Research Unit (NIHR HPRU) in Respiratory Infections at Imperial College London in partnership with Public Health England, as well as the NIHR HPRU in Immunisation at the London School of Hygiene and Tropical Medicine.